Response of Different Tomato Cultivars to Increase Cadmium Levels in Nutrient Culture - Yildiz, Nesrin; Aksu, Esra (Asian Journal of Chemistry, 2010)
The aim of this study was to determine the effect of increasing Cd levels (0, 0.05, 0.1, 0.5, 1, 2, 3, 5, 10, 20 μg g-1 Cd/pot) on plant dry matter, mineral contents and plant tolerance of different tomato cultivars (Inuictus lot 335 and Rio grande). Tomato seedlings were transferred into the nutrient solution and Cd was added into it. Plants were maintained in water culture for 8 week period. The test plants were harvested just before flowering. The results showed that increasing Cd levels in water culture had significant effect on dry matter contents in both tomato cultivars (p < 0.001). In general, the vegetative growth was better within a solution without Cd. With increasing Cd levels in nutrient solution, total P, Ca, Mg, K and Fe uptakes of plant decreased in both cultivars. However, Rio grande tomato cultivar was found more tolerable against Cd than Inuictus lot 335.